Productions of sense on agrochemicals exposure. The case of Young city (INNOTEC, 2017)
Uruguay has shown an increase in agricultural production and in agrochemical use over the last few years. Communities exposed to these substances have expressed concerns and doubts about these transformations. In this article part of the results of an investigation developed in Young city, Río Negro, Uruguay, are introduced. The main purpose of this paper is to describe and analyze how ambiental problems were delimited by community members, senses about territory, and conflicts over extensive agricultural production. From a cualitative approach, four social actor maps and five social cartografies were conducted. Members of community, statal authorities and actors related to agricultural production participated in these activities. The position of actors in the productive process influences productions of sense about agrochemicals. Those senses higlight exposition to this substances and other elements that take part on extensive agriculture. Subjective production and the possibilities of transforming vulnerabilities identified appear to be conditioned by reproduction of daily life.
Keywords: Pesticides; social perceptions; community